2019
DOI: 10.1186/s12911-019-0801-4
|View full text |Cite
|
Sign up to set email alerts
|

Predicting factors for survival of breast cancer patients using machine learning techniques

Abstract: BackgroundBreast cancer is one of the most common diseases in women worldwide. Many studies have been conducted to predict the survival indicators, however most of these analyses were predominantly performed using basic statistical methods. As an alternative, this study used machine learning techniques to build models for detecting and visualising significant prognostic indicators of breast cancer survival rate.MethodsA large hospital-based breast cancer dataset retrieved from the University Malaya Medical Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(117 citation statements)
references
References 43 publications
4
110
0
3
Order By: Relevance
“…To determine whether we can increase the test set prediction accuracy, we tested several other classification models ( 20 ) and compared the results to the classification by our seven-protein signature. Of the 276 proteins examined in the main cohort RPPA, 267 were also examined in the test set RPPA.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether we can increase the test set prediction accuracy, we tested several other classification models ( 20 ) and compared the results to the classification by our seven-protein signature. Of the 276 proteins examined in the main cohort RPPA, 267 were also examined in the test set RPPA.…”
Section: Resultsmentioning
confidence: 99%
“…In a clinical setting, the need for classification tools based on the prognostic stratification of GBM cases undergoing surgical protocols is of increasing importance. Numerous attempts have been developed to classify GBM patients, which include combination models of clinical, molecular and radiomic variables used in daily clinical practice [34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Ganggayah et al [5] used various classifiers on breast cancer data having 8066 record with 23 predictor and concluded that random forest classifier gives 82% better accuracy.…”
Section: Related Work Shanti and Raj Kumarmentioning
confidence: 99%